Exogenous nitric oxide‐induced postharvest disease resistance in citrus fruit to Colletotrichum gloeosporioides. (8th April 2015) - Zhou, Yahan; Li, Shunmin; Zeng, Kaifang
Abstract: BACKGROUND: Nitric oxide (NO) is an important signaling molecule involved in numerous plant responses to biotic and abiotic stresses. To investigate the effects of NO on the control of postharvest anthracnose caused by Colletotrichum gloeosporioides in citrus fruit and its possible mechanisms, citrus fruit were treated with an NO donor. RESULTS: The results showed that exogenous NO released from 50 µmol L −1 sodium nitroprusside aqueous solution could effectively reduce the disease incidence and lesion diameter of citrus fruit inoculated with C. gloeosporioides during storage at 20 °C. Exogenous NO could regulate hydrogen peroxide levels, stimulate the synthesis of phenolic compounds, and induce phenylalanine ammonia‐lyase, peroxidase, polyphenol oxidase, catalase activities, and the ascorbate–glutathione cycle. Furthermore, exogenous NO could inhibit weight loss, improve the ascorbic acid and titratable acidity content, and delay the increase in total soluble solids content in citrus fruit during storage at 20 °C. CONCLUSIONS: The results suggest that the use of exogenous NO is a potential method for inducing the disease resistance of fruit to fungal pathogens and for extending the postharvest life of citrus fruit. © 2015 Society of Chemical Industry